Analysis of Vertical Atmospheric Structure on the Formation of Convective Clouds and Heavy Rainfall in Padang Pariaman - Maharani, Trimike; Sudiar, Nofi Yendri; Amir, Harman; Zulhendra (Journal of Climate Change Society, 2025)
Padang Pariaman is one of the regions in West Sumatera that is highly vulnerable to hydrometeorogical disasters, particularly flooding caused by heavy rainfall. This study aims to analyze the influence of vertical atmospheric structure on the formation of convective clouds and heavy rainfall in the area. The data used include radiosonde observations and synoptic data from the Minangkabau Meteorological Station, as well as five atmospheric stability indices: Showalter Index (SI), K-Index (KI), Lifted Index (LI), Convective Available Potential Energy (CAPE), and Precipitable Water (PW). The study was conducted over one year, divided into four seasonal periods (DJF, MAM, JJA, SON). Multiple linear regression and correlation analysis were applied to evaluate the relationship between atmospheric indices and the occurrence of convective clouds and heavy rainfall. The results show that atmospheric instability generally increases during the DJF and MAM periods, as indicated by negative values of SI and LI, along with high values of CAPE and PW. These conditions support the development of Cumulonimbus clouds, which have the potential to produce heavy rainfall. Correlation analysis revealed a strong relationship between several stability indices—particularly CAPE and PW—and rainfall intensity. These findings suggest that analyzing vertical atmospheric structure using radiosonde data and RAOB indices can serve as an important early indicator in forecasting extreme weather events in Padang Pariaman.